INVESTIGATION OF DYNAMIC CHARACTERISTICS OF MULTI-BLADED S-SHAPED VANE TYPE ROTOR (Journal of Mechanical Engineering, 2014)
In the present research work the dynamic conditions of Multi S-shaped bladed rotor at different Reynolds number have been identified. The investigation on wind loading and aerodynamic effects on the four, five and six bladed S-shaped vertical axis vane type rotor has been conducted with the help of an open circuit subsonic wind tunnel. For different bladed rotor the flow velocities were varied from 5m/s to 9m/s covering the Reynolds numbers up to 1.35 x 105. It was experiential that by increasing the number of blades of rotor to the optimum limit considering all significant factors and at the same time by increasing its Reynolds number, the power output can be increased to its maximum level Finally, the nature of predicted dynamic characteristics has been examined by comparing with the existing research works. DOI: http://dx.doi.org/10.3329/jme.v44i1.19501